Identification of Potential Key Genes Associated With the Pathogenesis and Prognosis of Gastric Cancer Based on Integrated Bioinformatics Analysis - Liu, Xinkui; Wu, Jiarui; Zhang, Dan; Bing, Zhitong; Tian, Jinhui; Ni, Mengwei; Zhang, Xiaomeng; Meng, Ziqi; Liu, Shuyu (Frontiers in genetics, 2018)
Despite striking advances in multimodality management, gastric cancer (GC) remains the third cause of cancer mortality globally and identifying novel diagnostic and prognostic biomarkers is urgently demanded. The study aimed to identify potential key genes associated with the pathogenesis and prognosis of GC. Differentially expressed genes between GC and normal gastric tissue samples were screened by an integrated analysis of multiple gene expression profile datasets. Key genes related to the pathogenesis and prognosis of GC were identified by employing protein-protein interaction network and Cox proportional hazards model analyses. We identified nine hub genes ( , and ) which might be tightly correlated with the pathogenesis of GC. A prognostic gene signature consisted of , and was constructed with a good performance in predicting overall survivals. The findings of this study would provide some directive significance for further investigating the diagnostic and prognostic biomarkers to facilitate the molecular targeting therapy of GC.